New Chemicals and Routes for the Preparation of Gelatin/HA Composites using the Wet Precipitation Method - Nur Akbar; Asril Pramutadi Andi Mustari; Atiek Rostika Noviyanti (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2020)
Hydroxyapatite (HA) is a material that has many uses in a wide variety of applications such as bone repair, bone implants, and bone drug delivery systems. However, the main weakness of this material is its mechanical strength, which HA is not enough to be directly applied. Gelatin addition is used to improve the mechanical properties that can support material properties for the load-bearing application. This research aimed to obtain gelatin/HA composites with high mechanical strength. This goal is achieved by finding the optimum composite composition (addition of 20, 30, and 40% w/w gelatin), CaO precursors from chicken eggshells, and gradual composite preparation. The preparation of gelatin/HA composites was carried out using the wet precipitation method. The chemical bonding, the compressive strength of HA and gelatin/HA composites, and also morphologies were analyzed by Fourier Transform Infra-Red (FTIR), Universal Testing Machine, and Scanning Electron Microscopy (SEM) respectively. The FTIR spectra show there are chemical bonds between amide and carboxyl in gelatin and Ca2+ in HA. The best compressive strength obtained at the composition of 20% gelatin/HA composite is 99.3 MPa (meanwhile HA is 81.5 MPa). The addition of gelatin to HA increases the particle density; this contributes to the increase in mechanical strength.